Предмет: Математика,
автор: ilshatmusin
Решите уравнение:
(-х+3)•(х+4)=0
Спасибо!
Ответы
Автор ответа:
0
(-x+3)•(x+4)=0
-x²-4x+3x+12=0
-x²-1x+12=0
D=b²-4ac=(-1)²-4•(-1)•12=1+48=49 √49=7
x1=-b-√D/2a=1-7/-2=-6/-2=3
x2=-b+√D/2a=1+7/-2=8/-2=-4
-x²-4x+3x+12=0
-x²-1x+12=0
D=b²-4ac=(-1)²-4•(-1)•12=1+48=49 √49=7
x1=-b-√D/2a=1-7/-2=-6/-2=3
x2=-b+√D/2a=1+7/-2=8/-2=-4
Автор ответа:
0
(-х+3)•(х+4)=0, т.к. уравнение дано умножением, то каждый из множителей приравняем к 0, получим:
-х+3=0
и
х+4=0
решаем каждое новое уравнение:
-х+3=
-х=-3
х=3
и
х+4=0
х=-4
-х+3=0
и
х+4=0
решаем каждое новое уравнение:
-х+3=
-х=-3
х=3
и
х+4=0
х=-4
Похожие вопросы
Предмет: Алгебра,
автор: vladamaliavka
Предмет: Математика,
автор: sasaanaskevic
Предмет: Химия,
автор: firuza2287
Предмет: География,
автор: Хомяк26
Предмет: Литература,
автор: kraskova1954